Penerapan Eksperimen Sederhana untuk Meminimalkan Miskonsepsi IPA pada Materi Perubahan Wujud Benda - Theresia Indah; Wahyu Kurniawati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the nature of students’ misconceptions regarding the change of matter’s state and to determine the effectiveness of simple experiments in minimizing science misconceptions in elementary schools. The study employed a qualitative descriptive approach and was conducted in May 2026 at Timuran Elementary School. The research subjects consisted of 27 fifth-grade students, while 15 students were selected as interview samples to obtain more in-depth data. Data collection techniques were carried out through tests, observations, interviews, and documentation. Data analysis was performed inductively through the stages of data reduction, data presentation, drawing conclusions, and verification. The results of the study indicate that the highest rate of misconceptions occurred regarding the concept of crystallization at 47%, followed by evaporation at 40%, sublimation at 33%, and melting and condensation at 27%. Factors contributing to these misconceptions include students’ low prior understanding, teacher-centered instruction, a lack of practical activities, and difficulty understanding scientific terminology. The implementation of simple experiments helps students understand the concept of changes in the state of matter more concretely through direct observation, making students more active, interested, and able to connect science concepts to daily life. Thus, simple experiments can help minimize misconceptions in science learning in elementary school.